POWER QUALITY IMPROVEMENT USING ACTIVE POWER FILTER BASED ON FUZZY LOGIC CONTROLLER (International Journal of Engineering and Computer Science, 2014)
A fuzzy logic controller (FLC) with fast reference voltage generation with active power filter to correct and regulate unbalance voltage in three-phase system is proposed to improvement in power quality. The compensation algorithm is not based on three symmetrical components decomposition so the controller can yield a fast response that is essential in such a critical real time control work. The reference voltage is fed to the FLC, which is a robust closed loop controller. The proposed algorithm and control scheme of active power filter may correct and regulate unbalance voltage in three-phase system under different conditions of the utility of supply